The influence of single magnetic impurities on the conductance of quantum microconstrictions - Namiranian, A.; Kolesnichenko, Yu.A.; Omelyanchouk, A.N. (Физика низких температур, 2000)
The nonlinear ballistic conductance of three-dimensional quantum microconstrictions containing magnetic impurities is investigated. The nonlinear part of the conductance, which is due to the interaction of electrons with magnetic impurities, is obtained. The analytical results are analyzed numerically. It is shown that the intensity of the Kondo anomaly in the conductance as a function of the applied voltage depends on the diameter of the constriction and the positions of the impurities.